Japanese Foreign Policy at the Crossroads : Challenges and Options for the Twenty-First Century - Kawashima, Yutaka, 1942- (Book collections on Project MUSE., 2003)
"In Japanese Foreign Policy at the Crossroads, Yutaka Kawashima clarifies some of the defining parameters of Japan's foreign policy and examines the challenges it currently faces, including the quagmire on the Korean Peninsula, the future of the U.S.-Japan alliance, the management of Japan-China relations, and Japan's relations with Southeast Asia." "Kawashima - who, as vice minister of foreign affairs, was Japan's highest-ranking foreign service official - cautions Japan against attempts to ensure its security and well-being outside of an international framework. He believes it crucial that Japan work with as many like-minded countries as possible to construct a regional and international order based on shared interests and shared values. In an era of globalization, he cautions, such efforts will be crucial to maintaining global world order and ensuring civilized interaction among all states."--Jacket